ACS/WFC Pixel History, Bringing the Pixels Back to Science. Issue Volume 12:Issue S325(2016) (30th May 2017) - Borncamp, David; Grogin, Norman; Bourque, Matthew; Ogaz, Sara
Abstract: Excess thermal energy within a Charged Coupled Device (CCD) results in excess electrical current that is trapped within the lattice structure of the electronics. This excess signal from the CCD itself can be present through multiple exposures, which will have an adverse effect on its science performance unless it is corrected for. The traditional way to correct for this extra charge is to take occasional long-exposure images with the camera shutter closed. These images, generally referred to as "dark" images, allow for the measurement of thermal-electron contamination at each pixel of the CCD. This so-called "dark current" can then be subtracted from the science images by re-scaling to the science exposure times. Pixels that have signal above a certain value are traditionally marked as "hot" and flagged in the data quality array. Many users will discard these pixels as being bad. However, these pixels may not be bad in the sense that they cannot be reliably dark-subtracted; if these pixels are shown to be stable over a given anneal period, the charge can be properly subtracted and the extra Poisson noise from this dark current can be taken into account and put into the error arrays.